2012 Fourth International Workshop on Quality of Multimedia Experience 2012
DOI: 10.1109/qomex.2012.6263870
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel approach to subjective quality evaluation of conventional and 3D broadcasted video services

Abstract: Transmission errors are the main cause of degradation of the quality of real broadcasted video services. Therefore, knowing their impact on the quality of experience of the end users is a crucial issue. For instance, it would help to improve the performance of the distribution systems, and to develop monitoring tools to automatically estimate the quality perceived by the viewers. In this paper we validate a subjective evaluation approach specifically designed to obtain meaningful results of the effects of degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…These results show that subjects are able to effectively assess the video quality of individual QPs, and the content does not distract them from the task. This is in line with the results already reported in the literature for conventional 2D video and similar evaluation methodologies [42], [50], [51]. Furthermore, having the subjects engaged in the content increases the ecological validity of the quality evaluation compared to traditional methods [29], [52].…”
Section: Video Quality Assessmentsupporting
confidence: 89%
See 1 more Smart Citation
“…These results show that subjects are able to effectively assess the video quality of individual QPs, and the content does not distract them from the task. This is in line with the results already reported in the literature for conventional 2D video and similar evaluation methodologies [42], [50], [51]. Furthermore, having the subjects engaged in the content increases the ecological validity of the quality evaluation compared to traditional methods [29], [52].…”
Section: Video Quality Assessmentsupporting
confidence: 89%
“…The deadline to apply for an internship or exchange program for the whole year Quality. A Single-Stimulus Discrete Quality Evaluation (SSDQE) method [42] was applied to measure the quality in observers assigned to condition A. SSDQE uses long-duration contents to evaluate quality guaranteeing the continuity of the narrative. For this, the content is divided into segments, trying to mimic realistic situations of video consumption.…”
Section: International Officementioning
confidence: 99%
“…As an alternative to SSCQE, MIRO360 also implements the methodology proposed in [8], which has been labeled as Single Stimulus Discrete Quality Evaluation (SSDQE) in the context of this tool 2 . In this methodology, instead of continuously recording the quality level, it is periodically requested to the user while the video keeps playing on the background (Fig.…”
Section: A In-sequence Assessmentmentioning
confidence: 99%
“…In [61], the authors argue that the subjective test specified by the ITU may not simulate the home environment where the actual viewing is happening. In the standard ITU subjective test, short video sequences are often used, whose contents may not be interested to the viewers.…”
Section: E Subjective Test For 3d Videosmentioning
confidence: 99%
“…In the standard ITU subjective test, short video sequences are often used, whose contents may not be interested to the viewers. Therefore, in [61], the authors propose to use long video sequences, with the test methods shown in Fig. 11.…”
Section: E Subjective Test For 3d Videosmentioning
confidence: 99%